(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The emergence of enzyme-mimicking nanomaterials (nanozymes) represents a transformative development in biomedical research, offering catalytic versatility, enhanced stability, and cost-effective scalability compared to natural enzymes. This review consolidates current advances in the design, synthesis, and biomedical deployment of nanozymes, particularly those based on noble metals, metal oxides, and functional nanocomposites. A systematic comparative analysis was conducted across diverse studies to elucidate the catalytic mechanisms, structural-functional relationships, and environmental adaptability of these nanomaterials. The literature was critically evaluated with emphasis on the physicochemical factors governing nanozyme activity such as particle size, surface ligands, and crystal facets and their modulation strategies. Trends indicate that noble metal nanoparticles (e.g., Au, Pt, Pd) and metal oxides (e.g., Fe₃O₄, CeO₂, V₂O₅) exhibit peroxidase, oxidase, and catalase-like functions, with performance often surpassing their biological counterparts under physiological conditions. Moreover, 2D nanomaterials and Prussian blue analogues demonstrate significant promise as tunable catalytic platforms. Functionally, nanozymes are proving integral in areas such as tumor theranostics, antibacterial therapy, antioxidation, and bioorthogonal catalysis. Applications range from in situ ROS modulation for cancer treatment to programmable catalysis in cellular imaging and drug activation. Despite these advances, challenges remain in enhancing substrate specificity, minimizing cytotoxicity, and fully elucidating mechanistic pathways. In conclusion, nanozymes hold substantial potential to reshape therapeutic and diagnostic modalities. Future research must focus on integrating simulation-driven design, expanding the scope of enzyme mimicry, and ensuring biosafety in complex biological environments. Addressing these gaps could accelerate the clinical translation of nanozyme-based technologies, establishing them as cornerstone tools in next-generation biomedical applications.